Pediatric Resources. Issue 2 (2nd April 2016) - Petersen, David; Travis, Lisa D.
ABSTRACT: This column will focus on freely available online interactive resources for pediatrics. Four websites are examined that offer interactive experiences for studying various facets of the pediatric specialty. The websites vary in approach and emphasis, but many concentrate on case-based studies for learning the pediatric specialty. While useful for refreshing basic knowledge, these resources also teach, challenge, and inform advanced learners, thus making them suitable for medical students, residents, and clinicians.